Rebuilding public institutions together : professionals and citizens in a participatory democracy - Dzur, Albert W. (Cornell Selects, an imprint of Cornell University Press, 2018)
The Laurence and Lynne Brown Democracy Medal is an initiative of the McCourtney Institute for Democracy at Pennsylvania State University. It annually recognizes outstanding individuals, groups, and organizations that produce exceptional innovations to further democracy in the United States or around the world. In this book, Albert W. Dzur argues that some of the most innovative and important work in democracy is taking place face-to-face and isbeing led by professionals who bring those involved into the decisionmaking process. These "democratic professionals" create a culture thatleads to better decisions and overcomes what he calls "civic lethargy." He focuses on how this democratic professionalism manifests itself in the operation of a wide range of public institutions, including schools and local government, as well as in the reform of our criminal justice system, from juries to prisons